Vegetation Types of Sirohi Forest Division - Mathur, C. M.; Verma, S. K. (Indian Forester, 1964)
Attempts have been made to classify and describe the vegetation types of Sirohi Forest Division, situated in the south-west corner of Rajasthan, on the basis of proposed international classification for World Tropical Forest Types. In each vegetation type, degradation sub-types have been recognised in the form of physiognomic stages which are generally the result of biotic interference. Due to climatic and altitudinal changes, there is a considerable variation in the vegetation from thony species-Prosopis spicigera and Capparis decidua to evergreen species Mangifera indica and Syzygium cuminii with intermediate crops of Anogeissus pendula and Anogeissus latifolia.